Dopamine D(1) receptor involvement in latent inhibition and overshadowing - Nelson, Andrew J. D. (Cambridge University Press, 2012)
Latent inhibition (LI) manifests as poorer conditioning to a stimulus that has previously been experienced without consequence. There is good evidence of dopaminergic modulation of LI, as the effect is reliably disrupted by the indirect dopamine (DA) agonist amphetamine. The disruptive effects of amphetamine on LI are reversed by both typical and atypical antipsychotics, which on their own are able to facilitate LI. However, the contribution of different DA receptors to these effects is poorly understood. Amphetamine effects on another stimulus selection procedure, overshadowing, have been suggested to be D(1)-mediated. Thus, in the current experiments, we systematically investigated the role of D(1) receptors in LI. First, we tested the ability of the full D(1) agonist SKF 81297 to abolish LI and compared the effects of this drug on LI and overshadowing. Subsequently, we examined whether the D(1) antagonist SCH 23390 can lead to the emergence of LI under conditions that do not produce the effect in normal animals (weak pre-exposure). Finally, we tested the ability of SCH 23390 to block amphetamine-induced disruption of LI. We found little evidence that direct stimulation of D(1) receptors abolishes LI (although there was some attenuation of LI at 0.4 mg/kg SKF 81297). Similarly, SCH 23390 failed to enhance LI. However, SCH 23390 did block amphetamine-induced disruption of LI. These data indicate that, while LI may be unaffected by selective manipulation of activity at D(1) receptors, the effects of amphetamine on LI are to some extent dependent on actions at D(1) receptors.